The lost compass – study about the evaluation, self-image and productivity (Training and Practice : Journal of Educational Sciences, 2020)
The certificate for primary school students can hide several years of difference at the same grade and the same mark. This deceptive output brings a distorted self-image and decreased social productivity. The literature on summative and formative assessment is complicated and its practice is controversial. The contradiction is exacerbated by the high pressure on teachers – towards a more favorable grade, but not worse than enough. The present study is a quantitative research based on qualitative antecedents, which was conducted on pedagogical evaluation and its comparison methods. Based on our research, it is likely true that the comparison to the members of the student group has a much greater emphasis in the year-end classification than paying attention to the subject requirements. The expectations of the adult environment affect the child almost from birth. During socialization, children more or less learn to conform to these. Self-image of school success is an important factor, but it would be difficult to determine exactly how much this matters for school performance (Cserné, 1997).